تقييم استجابة بعض طرز الشعير (Hordeum vulgare L.) تحت ظروف الإجهاد الملحي في الليزيميترات (Damascus University Journal of agriculture sciences, 2022)
The experiment was carried out in the greenhouse of the Center for Biological Control at the Faculty of Agriculture, Damascus University, during the growing season 2019-2020, in order to evaluate the response of six barley genotypes (H17, H9, H20, Arabi Aswad, Furat6, Furat7) for NaCl–induced salinity stress tolerance in lysimeters, depending on some physiological and biochemical traits. The experiment was conducted according to simple randomized block design with three replications. Results showed that the average relative water content was significantly higher in the control (without salt stress) for the barley genotypes Furat6 and H9 (89.87 and 88.91%, respectively), while it was significantly the lowest in the 200 mM NaCl salinity stress treatment for the genotypes H17, Furat7 and H20 (79.07, 77.92, 73.56% respectively). The average percentage of solutes leaked through the cytoplasmic membranes was significantly the highest of in the higher salinity level for the genotypes H9, H17, Furat7, and Arabi Aswad without significant differences among them (87.85, 86.85, 83.35, 74.05%, respectively). However, it was significantly the lowest in the control treatment for the genotypes Arabi Aswad, H9, and H20 without significant differences among them (44.40, 46.11 and 48.91%, respectively). The average proline content was significantly the highest in the higher salinity level (200 mM NaCl) for the genotypes Furat6, H20, and Arabi Aswad without significant differences among them (2.825, 2.707, and 2.497 μg. g-1 green matter respectively), while it was significantly the lowest in the control for all the remaining studied barley genotypes without significant differences among them. The average of potassium to sodium ratio was significantly the highest in the control for H9, Arabi Aswad and H20 genotypes without significant differences among them (7.28, 6.77 and 5.30 respectively). While it was significantly the lowest when the treatment investigated salinity stress level (200 mM NaCl) for the genotypes H20, Furat7 and H9 without significant differences among them (0.41, 0.60, and 0.96 respectively). Generally, it has been found that the genotypes Furat6, Araby Aswad and H20 could maintain relatively high values of relative water content in the leaves, and were capable of producing significantly higher amount of proline and maintained the integrity of the cytoplasmic membranes and a high percentage. From potassium to sodium ratio, indicating the importance of these traits in improving tolerance to salt stress.
Keywords: Salinity stress; Relative water content; Membrane integrity; Proline; Barley